Zeros, Poles, and Fixed Points of Meromorphic Solutions of Difference Painlevé Equations - Shuang-Ting Lan; Zong-Xuan Chen (Abstract and Applied Analysis)
In this paper, we mainly study the properties of transcendental meromorphic solutions f(z) of difference Painlevé equations w(z+1)w(z-1)(w(z)-1)=η(z)w2(z)-λ(z)w(z) and w(z+1)w(z-1)(w(z)-1)=η(z)w(z) and obtain precise estimations of the exponents of convergence of zeros, poles of Δf(z) and Δf(z)/f(z), and of fixed points of f(z+c) for any c∈ℂ.